2010
DOI: 10.1007/s12144-010-9086-6
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Ideology, Economic Conservatism, and Causal Attributions for Poverty and Wealth

Abstract: The purpose of the study is to analyze the effects of different features of Conservative Ideology, measured via the Social Dominance Orientation (SDO), Right-Wing Authoritarianism (RWA) and Economic Conservatism (EC) scales, on Internal and External casual attributions for poverty and wealth. Participants were a group of 181 university students. Results of multiple regression analyses suggested that EC influenced Internal causal attributions for poverty and wealth positively but influenced the External ones ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 28 publications
3
34
0
7
Order By: Relevance
“…Republicans/Conservatives held more negative feelings and stereotypes about the poor; they are also more likely to make internal attributions for poverty. Another survey by Bobbio et al (2010) examined the effects of various aspects of Conservative Ideology, as measured through the Social Dominance Orientation (SDO), Right Wing Authoritarian (RWA) and Economic Conservatism (EC) scales, on the causal attributions (Internal-Individualistic versus External-Structuralist) for poverty and wealth. Multiple regression analyses showed that EC is the most significant predictor of attributions for poverty and wealth.…”
Section: Attitudes Towards the Poormentioning
confidence: 99%
See 1 more Smart Citation
“…Republicans/Conservatives held more negative feelings and stereotypes about the poor; they are also more likely to make internal attributions for poverty. Another survey by Bobbio et al (2010) examined the effects of various aspects of Conservative Ideology, as measured through the Social Dominance Orientation (SDO), Right Wing Authoritarian (RWA) and Economic Conservatism (EC) scales, on the causal attributions (Internal-Individualistic versus External-Structuralist) for poverty and wealth. Multiple regression analyses showed that EC is the most significant predictor of attributions for poverty and wealth.…”
Section: Attitudes Towards the Poormentioning
confidence: 99%
“…It will use the Moral Foundations Theory (MFT) to present a more nuanced understanding of individuals' attitudes towards the poor, as well as extend the existing studies that have utilized moral intuitions as psychological mechanism to explain people's positions and attitudes on social issues (Koleva et al 2012). Additionally, the paper aims to enrich the current literature examining public's perception of the poor which has been dominantly analyzed via the variable of socio-political ideologies (e.g., Bobbio et al 2010;Rudolph and Evans 2005;Zucker and Weiner 1993). At the outset, the current study will discuss MFT and how it has been used to explain people's opinions on polarizing issues such as abortion, gay marriage, and stem cell research (Koleva et al 2012); socio-political beliefs (Federico et al 2013); and moral rhetoric of decision-makers and interest groups (Clifford and Jerit 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The 14-item SRWA (Manganelli Rattazzi, Bobbio, & Canova, 2007) was created by factoring Altemeyer's (1996) 30-item RWA scale into two subscales measuring Authoritarian Aggression and Submission (SRWA-A) and Conservatism (SRWA-C). Each subscale has acceptable reliability and correlates highly with the original 30-item RWA scale (Bobbio, Canova, & Manganelli, 2010). Higher scores on either subscale reflect greater levels of RWA.…”
Section: Self-esteem Scale (Ses)mentioning
confidence: 99%
“…While several studies have shown that authoritarian individuals tend to support conservative economic policies (Bobbio, Canova, & Manganelli, 2010;Cornelis & Van Hiel, 2006;Everett, 2013;Jost, Blount, Pfeffer, & Hunyady, 2003;Napier & Jost, 2008;Van Hiel, Pandelaere, & Duriez, 2004), other studies have found that authoritarianism is associated with greater support for interventions related to the economy (Radkiewicz, 2017;Van Hiel & Kossowska, 2007), protectionism (Johnston, 2013), government redistribution in the general population (Calzada, G omez-Garrido, Moreno, & Moreno-Fuentes, 2014;Staerkl e, Likki, & Scheidegger, 2012), and government redistribution in favor of ethnic in-groups (Mewes & Mau, 2012). While several studies have shown that authoritarian individuals tend to support conservative economic policies (Bobbio, Canova, & Manganelli, 2010;Cornelis & Van Hiel, 2006;Everett, 2013;Jost, Blount, Pfeffer, & Hunyady, 2003;Napier & Jost, 2008;Van Hiel, Pandelaere, & Duriez, 2004), other studies have found that authoritarianism is associated with greater support for interventions related to the economy (Radkiewicz, 2017;Van Hiel & Kossowska, 2007), protectionism (Johnston, 2013), government redistribution in the general population (Calzada, G omez-Garrido, Moreno, & Moreno-Fuentes, 2014;Staerkl e, Likki, & Scheidegger, 2012), and government redistribution in favor of ethnic in-groups (Mewes & Mau, 2012).…”
Section: Right-wing Authoritarianism and Attitudes Toward Redistributionmentioning
confidence: 99%